2022
DOI: 10.1523/eneuro.0310-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence-Dependent Effects of Long-Access Cocaine Self-Administration on Nucleus Accumbens Astrocytes Are Observed in Male, But Not Female, Rats

Abstract: Accumulating evidence indicates significant consequences for astrocytes associated with drug abuse. For example, reductions in structural features and synaptic colocalization of male rat nucleus accumbens (NAc) astrocytes are observed following short-access (ShA, 2 hours/day) self-administration and extinction from cocaine, methamphetamine, and heroin. However, it is unknown whether these observations extend to other rodent models of drug abuse, how enduring these effects may be, and whether similar effects ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Both Tat and cocaine exposure independently alter astrocyte metabolism, resulting in reduced lactate transport to neurons, suggesting HIV-1 proteins may drive impairments in neuronal function indirectly through dysregulation of astrocytes (Natarajaseenivasan et al, 2018). We and others speculate that targeting astrocytes as regulators of dysregulated reward seeking behavior will be a promising therapeutic strategy across classes of addictive drugs (Sco eld et al, 2015; Walker et al, 2020; Kim et al, 2022;Kruyer et al, 2022). The current ndings suggest that astrocyte dysregulation is common across models of HIV, including infection and protein expression models, suggesting that astrocyte function and structure may further be promising for reversing HIV-associated changes in drug seeking behavior.…”
Section: Discussionmentioning
confidence: 67%
“…Both Tat and cocaine exposure independently alter astrocyte metabolism, resulting in reduced lactate transport to neurons, suggesting HIV-1 proteins may drive impairments in neuronal function indirectly through dysregulation of astrocytes (Natarajaseenivasan et al, 2018). We and others speculate that targeting astrocytes as regulators of dysregulated reward seeking behavior will be a promising therapeutic strategy across classes of addictive drugs (Sco eld et al, 2015; Walker et al, 2020; Kim et al, 2022;Kruyer et al, 2022). The current ndings suggest that astrocyte dysregulation is common across models of HIV, including infection and protein expression models, suggesting that astrocyte function and structure may further be promising for reversing HIV-associated changes in drug seeking behavior.…”
Section: Discussionmentioning
confidence: 67%
“…Extending these studies, we demonstrated the time-dependent increase of methamphetamine seeking after abstinence was independent of the estrous cycles, and Fos expression in DMS and AIT-L was independent of either sex or estrous cycles. Overall, our data suggest that in contrast to cocaine [ 34 39 ], the estrous cycle is not a critical factor that influences incubation of methamphetamine craving and the role of AIT-L and DMS in methamphetamine relapse, at least in terms of circuit activity, might generalize across sexes and estrous cycles in female rats.…”
Section: Discussionmentioning
confidence: 70%
“…Sex differences in incubation of cocaine craving are indeed attributed to the effect of estrous cycle with estrus females exhibiting higher cue-induced cocaine seeking after prolonged abstinence than non-estrus females [ 34 36 ]. Further, recent studies demonstrated sex- and estrous cycle-dependent neural mechanisms underlying incubation of cocaine craving [ 37 39 ]. For example, inhibition of metabotropic glutamate receptor 5 (mGlu5) in basolateral amygdala (BLA) prevents incubated cocaine seeking in estrus-female, but not in non-estrus female or male rats [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is important to note that only male mice were tested here, and the results may therefore be restricted to only males. Indeed, there are sex differences in the temporal pattern of cocaine seeking across abstinence, as well as associated corticolimbic cellular adaptations (Kim et al, 2022; Towers et al, 2023), though this may depend on estrous phase (Corbett et al, 2021). Thus, examination of sex differences in cocaine seeking across the various factors and levels of analysis tested here represents an important future direction of this work.…”
Section: Discussionmentioning
confidence: 99%